Responding to ‘image-based domestic abuse’ - Welsh, Kirsty (International journal of law, crime and justice, 2023)
This paper questions whether the law is equipped to respond to the range of behaviours that characterise domestic abuse, especially those behaviours that are associated with coercion and control and, in particular, the disclosure of private sexual images to this end. A willingness to recognise notions of intimate terrorism and coercive control as an integral part of this gendered harm has now been embedded in our legislative regime through the enactment of s.76 Serious Crime Act. Alongside, s.33 Criminal Justice and Courts Act 2015 has criminalised so-called ‘revenge porn’ through prohibiting the disclosure of intimate sexual images. In this paper, I argue that neither of these offences truly reflect the experiences of women and both involve barriers to justice. In particular, I argue that, where coercion and the disclosure of private sexual images/threats to disclose the same, or other demeaning images coincide, the legal framework is particularly ill-equipped to respond.